Rating of perceived effort but relative to what? A comparison between imposed and self-selected anchors. (May 2023) - Malleron, Tomer; Har-Nir, Itai; Vigotsky, Andrew D.; Halperin, Israel
Abstract: Purpose: Collecting reliable and valid rating of perceived effort (RPE) data requires properly anchoring the scales' upper limits ( i.e., the meaning of 10 on a 0–10 scale). Yet, despite their importance, anchoring procedures remain understudied and theoretically underdeveloped. Here we propose a new task-based anchoring procedure that distinguishes between imposed and self-selected anchors. In the former, researchers impose on participants a specific task as the anchor; in the latter, participants choose the most effortful task experienced or imaginable as the anchor. We compared the impact of these conceptually different anchoring procedures on RPE. Methods: Twenty-five resistance-trained participants (13 females) attended a familiarization and two randomized experimental sessions. In both experimental sessions, participants performed non-fatiguing and fatiguing isometric maximal voluntary contraction (MVC) protocols with the squat followed by the gripper or vice versa. After each MVC, participants reported their RPE on a 0–10 scale relative to an imposed anchor of the performed task ( e.g., gripper MVCs anchored to a gripper MVC) or to a self-selected anchor. Results: In the non-fatiguing condition, imposed anchors yielded greater RPEs than self-selected anchors for both the squat [on average, 9.4 vs. 5.5; Δ(CI95% ) = 3.9 (3.2, 4.5)] and gripper [9.4 vs. 3.9; Δ = 5.5 (4.7, 6.3)]. Similar results were observed in the fatiguing condition for both the squat [9.7 vs. 6.9; Δ = 2.8 (2.1, 3.5)] and gripper [9.7 vs. 4.5; Δ = 5.2 (4.3, 5.9)]. Conclusions: We found large differences in RPE between the two anchors, independent of exercises and fatigue state. These findings provide a basis for further development and refinement of anchoring procedures and highlight the importance of selecting, justifying, and consistently applying the chosen anchors. Highlights: Using RPE scales requires one to properly anchor the scales' upper limit. Anchoring procedures remain understudied and theoretically underdeveloped. We developed and compared the impact of a new task-based anchoring procedure. We found large differences in ratings between the two anchoring approaches. Researchers should consistently apply and report the chosen anchoring procedure.